Address to the U.N. Economic and Social Council, New York, October 28, 1971 - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank Group, reports that the Bank is operating at a high level of activity. During the first decade, the developing nations succeeded in adding a substantial increment to their very low levels of material wealth and their average rate of growth was appreciably higher at the end of the decade than it had been at the beginning. He suggests that development is not merely the size of the economy, but the quality of life for each member of society. The pursuit of this objective has deep-reaching implications. It is no longer sufficient to strain simply for growth of output. Development has to be seen as a composite of many factors that come together into an effective relationship. It’s a task of great subtlety and complexity. He says that the problems of population, nutrition and employment need higher priority. He recommends a twofold strategy to address these problems. One, efforts to encourage and assist family planning need to be intensified. Second, development programs need to be reshaped to take into account that population is growing rapidly. He concludes that if the work of the U.N. and Bank makes it possible that fewer children die and fewer parents grieve, that there is less poverty and more hope, that there is less waste and more realization of life’s potential, this will be a better and a more peaceful world.